Interaction of Taguchi Design with Quantitative Analysis of Crystalline Phase in Triaxial Ceramic Employing Palm Oil Fuel Ash Application. (January 2019) - Hassan, M F; Zainudin, A; Sia, C K; Ong, P; Narong, O L C; Yee, S K; Nor, N H M; Katimon, M N
Abstract: Application of triaxial ceramic commonly performed by crystalline phase analysis using X-ray diffraction (XRD) analysis. In this paper, Taguchi L18 orthogonal array layout was used as an experimental design to perform quantitative analysis of crystalline phase test. Palm Oil Fuel Ash (POFA) was employed as a secondary filler material in the triaxial ceramic composition. The parameters investigated were the type of POFA, POFA composition, molding pressure, sintering temperature, and soaking time. Meanwhile, the responses analyzed include the percentage of mullite and albite phases, where it was objected by criterion higher is better and smaller is better, respectively. The Taguchi design analysis had suggested that the highest mullite and smallest albite phase specimens were obtained at 5 wt. % of unground POFA (GPOFA), 3-ton (4-ton for albite phase) of molding pressure, 1200 °C of sintering temperature, and 180 min of soaking time.